The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/uog.6257
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional ultrasound diagnosis of cleft palate: ‘reverse face’, ‘flipped face’ or ‘oblique face’–which method is best?

Abstract: Objectives To compare the performance of three sonographic techniques, the 'reverse-face ', 'flipped-face' and 'oblique-face' methods, for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
57
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 15 publications
0
57
0
1
Order By: Relevance
“…Tonni et al 5 have demonstrated that 3DUS have enhanced the diagnostic accuracy in detecting cleft lip (CL) and cleft palate (CP) in a routine second trimester scan on low-risk pregnant women. To enhance prenatal detection of CL/CP, different 3DUS techniques as the "reverse face" 10 , the "flipped" face 11 , the "oblique" 12 and the "angle insonation" 13 view have been developed and proposed for inclusion into clinical obstetrics practice.…”
mentioning
confidence: 99%
“…Tonni et al 5 have demonstrated that 3DUS have enhanced the diagnostic accuracy in detecting cleft lip (CL) and cleft palate (CP) in a routine second trimester scan on low-risk pregnant women. To enhance prenatal detection of CL/CP, different 3DUS techniques as the "reverse face" 10 , the "flipped" face 11 , the "oblique" 12 and the "angle insonation" 13 view have been developed and proposed for inclusion into clinical obstetrics practice.…”
mentioning
confidence: 99%
“…A number of techniques for fetal palate imaging have been developed. These include the ''flipped-face'' view (Platt et al 2006), the ''reverse-face'' view (Campbell and Lees 2003), the Faure technique (Faure et al 2007), ''angle insonation'' (Pilu and Segata 2007), ''obliqueface'' view (Martinez Ten et al 2009) and retronasal triangle (Sepulveda et al 2010). The last technique has been applied for imaging the fetal palate at the first-trimester scan.…”
Section: -Dus In the Diagnosis Of Cleft Lip And Cleft Lip/palatementioning
confidence: 99%
“…Faure et al (2007), however, did not produce images involving facial clefting. Martinez-Ten et al (2009) studied 60 fetuses between 20 and 33 wk of gestation, of which 10 had a cleft lip and palate initially detected by conventional 2-DUS at second-trimester scan. These authors reported that ''oblique view'' was the best method when the palate was involved (100%), whereas the ''reverse-face'' and ''flipped-face'' views were able to diagnose this area correctly in 71% and 86% of cases, respectively.…”
Section: -Dus In the Diagnosis Of Cleft Lip And Cleft Lip/palatementioning
confidence: 99%
See 1 more Smart Citation
“…68 Since then, several publications have reported improvements using different techniques in the imaging of cleft of the alveolar ridge of the maxilla, cleft lip and palate, and cleft of the palatine bone. [69][70][71][72][73][74] Three-dimensional ultrasound seems to perform better than bi-dimensional ultrasound in the diagnosis of cleft anomalies. 8,62,[75][76][77] Ultrasound visualization of the maxilla and palatine bone suffers with several technical difficulties.…”
Section: Imaging Of the Hard Palatementioning
confidence: 99%